On the Kiguradze theorem for linear boundary-value problems - Mikhailets, V.А.; Pelekhata, O.B.; Reva, N.V. (Reports of the National Academy of Sciences of Ukraine, 2017)
We investigate the limiting behavior of solutions of inhomogeneous boundary-value problems for the systems of linear ordinary differential equations on a finite interval. A generalization of the Kiguradze theorem (1987) on the passage to the limit is obtained.